Bottom-up childcare in a top-down welfare state: explaining cooperative organization among Swedish parents. Issue 1 (2nd January 2016) - Vamstad, Johan
ABSTRACT: Almost all children in Sweden spend at least some part of their early childhood in organized childcare, primarily in the form of preschools. About 10% of all preschools in Sweden are parent cooperatives, which make the childcare area an anomaly in the Swedish welfare state; no other service area has such a significant proportion of cooperative service providers. The parent cooperatives are initiated by the parents themselves, they are social enterprises created from the bottom-up. Why do parents decide to start a parent cooperative preschool in a welfare state where childcare is considered a social right and a responsibility for the state? This article will explore several different motives for starting parent cooperatives in Sweden, with special attention to the role of the public sector and political decisions. The findings are based on an extensive empiric study performed between the years 2003 and 2007.